Cultural Perception on Prosperity Gospel Teaching and its Ramification on Whole-Life Stewardship: A Case of Africa Gospel Church in Kampala, Uganda - Ouma, James (International Journal of Science and Research, 2019)
The objective of this study was to determine the cultural perception on Prosperity Gospel Teaching (PGT) among members of Africa Gospel Church (AGC) in the Kampala area and its ramification on whole-life stewardship. The study was guided by a crosssectional survey research design on a target population that comprised of 923 church members. Simple random sampling procedure was designated for the lay members while purposive sampling applied to the lay leaders and pastors. The sample size of this study was 279 respondents from seven AGCs in Kampala area, who included; 216 lay members, 14 pastors, and 49 lay leaders. The research instruments adopted in the study were questionnaires and Focus Group Discussions (FGD) to collect data, which was analysed using SPSS version 25. Findings from the study revealed that AGC members and PGT share many similar features on wealth. However, the features tend to contravene the fundamental Christian doctrine on whole-life stewardship. Consequently, this promotes syncretistic tendencies which are unhealthy in promoting whole-life stewardship among the congregants. The study therefore recommends that AGC appraises its cultural values on wealth in light of the Scriptures, encourage the biblical knowledge and discussions on contextual theology of stewardship; conduct seminars and workshops and share series of sermons on good stewardship, have Bible study on proper use of God’s resources, develop and equip members with practical skills that will advance relevant application of God’s gifts in the church and society
free